Giant axillary mass diagnostic of sarcomatoid carcinoma of unknown primary (SCUP) - Bono Puertes, Vicente; Orozco Gil, Natalia; Díaz del Río, Manuel; Moreno Torres, Beatriz; Seguí Gregori, Jesús (Cirugía del Uruguay, 2025)
Sarcomatoid carcinoma of unknown primary (SCUP) is a rare tumor entity that combines epithelial and mesenchymal components, without identification of its primary site. We present the case of a 78-year-old woman, with a history of superficial melanoma (2015), bladder carcinoma (radical cystectomy in 2017), frontal basal cell carcinoma (2021), and ulcerated squamous cell carcinoma of the shoulder (2022). In 2024, she presented with asthenia, anorexia, and a hard right axillary mass, adherent to deep planes. Ultrasound and CT revealed a large lobulated lesion with malignant features. Core needle biopsy reported axillary lymph node infiltrated by anaplastic large-cell carcinoma. Surgical excision was performed; the mass, very friable, ruptured during manipulation, achieving an R2 resection due to risk of vascular injury. Histological examination revealed spindle and epithelioid cells with pleomorphic nuclei, abundant mitoses, apoptosis, and necrosis, positive for vimentin and CD10, with focal positivity for muscle-specific actin, CK A1-A3, CAM5.2, GATA3, P40, and CK19. A diagnosis of SCUP was established, possibly as a dedifferentiated metastasis of bladder carcinoma (focal GATA3 positivity) or cutaneous squamous carcinoma (focal P40 positivity), ruling out pulmonary, gastrointestinal, or melanocytic origin. SCUP is usually diagnosed at metastatic stages, with predilection for lymph nodes, bone, lung, and liver. It has a poor prognosis, with a median survival of less than one year, and poor response to chemotherapy (gemcitabine-docetaxel). Immunohistochemistry is essential to guide diagnosis, although often inconclusive. Molecular biology could provide therapeutic options in the future. In this case, due to persistent tumor, frailty, cognitive decline, and comorbidities, active treatment was ruled out, opting instea